Implementasi Manajemen Teknologi Informasi Perpustakaan Universitas Dian Nusantara dengan COBIT 5 - Shidqi, Fauzan; Widianti, Linda Wahyu (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2024)
Information technology (IT) management at Dian Nusantara University library aims to improve the efficiency and quality of IT-based services through the implementation of Senayan Library Management System (SLiMS). This research uses the COBIT 5 framework to evaluate IT governance in seven sub-domains, namely EDM04, APO04, APO07, APO13, BAI04, DSS01, and MEA01. The research method used was a quantitative approach with data collection through an online questionnaire to 10 respondents, including the bureau chief and library staff. The analysis results show that the average maturity index for each sub-domain ranges from 3.8 to 4.2, indicating a good to excellent level of IT management. However, there is still a gap between the current maturity level and the expected level, which is at level 5. Some aspects that require improvement include policy reporting, risk documentation, security policy updates, project evaluation, and SLA implementation. Based on the results of the study, strategic measures such as increased human resource training, policy updates, development of escalation procedures, and improved performance evaluation mechanisms are recommended. With the implementation of these recommendations, it is expected that the library can achieve an optimal level of IT management maturity, supporting more effective and efficient information technology-based services.